Global profiling of polyketide synthases in facultative multicellular eukaryotes - Markus Günther; Rosa Herbst; Nico Ueberschaar; Daniela Hildebrandt; Lisa Reimer; Pierre Stallforth (Proceedings of the National Academy of Sciences, 2025)
Polyketides represent a structurally diverse class of natural products with a wide range of biological functions, including antimicrobial activity, defense responses, developmental regulation, pigmentation, and intercellular and intracellular communication signals. The social amoeba Dictyostelium discoideum harbors 40 polyketide synthase (PKS) genes, yet the specific and collective functions remain poorly understood. PKSs require activation by the phosphopantetheinyl transferase DiSfp, which converts inactive apoenzymes into functional holo forms. Disruption of the DiSfp gene abolished the production of PKS-derived metabolites across all developmental stages. Integrated phenotypic, transcriptomic, and metabolomic analyses revealed impaired growth in liquid culture, defects in macropinocytosis, aberrant chemotaxis, and diminished spore formation, associated with altered expression of genes regulating these processes. Comparative metabolomic profiling of the mutant identified candidate polyketide metabolites across different developmental stages, providing a valuable resource for targeted identification and isolation of previously undescribed compounds. This study establishes a functional link between the PKS machinery and the metabolic and developmental networks of D. discoideum , highlighting the essential roles of polyketides in cellular physiology and offering a framework for future polyketide discovery.